Comparison of cone and cone shell configuration for depth sensitive fluorescence measurements in turbid media - Ong, Yi Hong (2014)
We have developed a novel cone shell illumination and detection configurations using combination of axicon lenses for depth sensitive fluorescence spectroscopy. The probe was demonstrated experimentally to be able to selectively detecting fluorescence from different depths from a two-layered turbid agar phantom. In addition to enhanced contrast of subsurface fluorescence measurement as compared to a conventional cone configuration implemented by a microscope objective lens, the axicon lenses based setup eliminated the need of moving the objective lens up or down to achieve depth sensitive measurements, which effectively improves the consistency of optical coupling thus would be preferred in a clinical setting.